Multifunctional magnetic nanoparticles for enhanced intracellular drug transport1. Issue 20 (28th May 2015) - Tudisco, C.; Cambria, M. T.; Sinatra, F.; Bertani, F.; Alba, A.; Giuffrida, A. E.; Saccone, S.; Fantechi, E.; Innocenti, C.; Sangregorio, C.; Dalcanale, E.; Condorelli, G. G.
<x xml:space="preserve">Abstract</x> New multicomponent biocompatible MNPs are designed as intracellular vectors to in situ load antitumor drugs and transport them inside cells.